TEACHING NARRATIVE READING BY USING PAIRED STORYTELLING TECHNIQUE TO THE EIGHTH GRADE STUDENTS AT SMP ADABIYAH PALEMBANG - Weni Pratiwi (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2016)
The objectives of the study were to find out whether or not there was a significant difference between the eighth grade students’ narrative reading achievement who were taught by using paired storytelling technique and those who were not and to find out whether or not there was a significant improvement on the eighth grade students’ narrative reading achievement taught by using paired storytelling technique at SMP Adabiyah Palembang. The population of this study consisted of 163 students of SMP Adabiyah Palembang in the academic year 2015/2016. There were 64 students taken as sample. Each class consisted of 32 students from class VIII 2 as control group and class VIII 3 as experimental group. The instrument in measuring students’ narrative reading achievement was administered twice, as the pretest and posttest for both experimental and control group. The results of the test were analyzed by using independent sample t-test and paired sample t-test. From the result of the independent sample t-test, it was found that there was a significant difference from students’ posttest experimental and control group, since the p-output (0.000) was lower than 0.05 and t-obtained (3.986) was higher than t-table (1.9989). From the result of the paired sample t-test, it was found that there was a significant improvement on students’ narrative reading achievement who were taught by using paired storytelling technique, since the p-output (0.000) was lower than 0.05 and t-obtained (26.351) was higher than (2.0395).